Building a training program to develop auditory perception among students of the Institute of Fine Arts, in the subject of music and chanting (Journal of the College of Basic Education, 2022)
This study aimed at building a training program to develop auditory perception among students of the Institute of Fine Arts in the subject of music and chanting. To achieve the goal of the research، the researcher used the experimental method on a sample of second-grade students from the Institute of Fine Arts، and the research sample consisted of (50) students divided equally into two groups، one of them is control and the other is experimental. The researcher used a knowledge achievement test (pre and post)، as well as a performance evaluation form. To access the research results، the researcher used a group of (statistical methods، including: The t-test (t-test) for two independent samples. This test was used for equivalence in the research variables، namely (chronological age - previous experience) between members of the two experimental and control groups. Paragraph difficulty equation: This equation was used to identify the degree of difficulty of achievement test items. Paragraph discrimination equation. This equation was used to find the distinction of achievement test items. Effectiveness of alternatives: It was used to calculate the effectiveness of incorrect (false) alternatives for achievement test items. Alpha Cronbach equation was used to calculate the reliability coefficient of achievement test. Pearson correlation coefficient. This equation was used to calculate the reliability of the skill performance questionnaire.The results of the study showed the superiority of the experimental group over the control group in the two dimensional cognitive and skill tests، and the presence of an effect of the training program. The researcher recommended several recommendations، including:Including the auditory perception skills reached by the study in the music and chanting curriculum for the second grade in fine arts institutes.Urging teachers to use the learning program for auditory perception and training them in preparing educational programs alongside the textbook. To complete the current research، the researcher suggested several proposals، including: Conducting a similar study for students of the Faculties of Basic Education / Department of Art Education